Direct Oral Anticoagulants for Prevention of Venous Thromboembolism after Cancer-related Surgery: Systematic Review and Network Meta-analysis - Pititto, Gerardo N.; Maraziti, Giorgio; Squizzato, Alessandro; Becattini, Cecilia (Thrombosis and Haemostasis, 2025)
The risk of venous thromboembolism (VTE) is high after cancer surgery and is reduced by antithrombotic prophylaxis.We conducted a systematic review and network meta-analysis to evaluate the effectiveness and safety of direct oral anticoagulants (DOACs) for VTE prophylaxis after cancer surgery. The primary study outcome was 30-day VTE after surgery. Pooled odds ratios (ORs) and corresponding 95% confidence intervals (CIs) were estimated.Five randomized controlled trials (RCTs; two gynecological, one abdominal, one neurosurgical, and one thoracic; 1,694 patients) and seven observational studies (three urological, two abdominal, and two gynecological; 2,042 patients) were included. DOACs reduced the incidence of 30-day (OR 0.52, 95% CI 0.27-0.98, I2 22.7%) and 90-day VTE (OR 0.51, 95% CI 0.28-0.92, I2 0%) compared to LMWH. No difference was observed between DOACs and LMWH in 30 and 90-day bleeding outcomes. In random effect analyses, apixaban (OR 0.31, 95% CI 0.11-0.84) and not rivaroxaban reduced the risk of 30 day-VTE compared to LMWH (OR 0.69, 95% CI 0.35-1.34) without increasing the risk of bleeding at 30 or 90 days. No difference in the risk of VTE or bleeding was observed between DOACs and placebo/no treatment, but these analyses were probably underpowered. Subgroup analyses were conducted on LMWH pre-treatment, extended prophylaxis, duration of surgery, and type of surgery.Our study supports apixaban and rivaroxaban as promising alternatives to LMWH in post-operative prophylaxis of VTE after cancer surgery. Further high-quality data are needed in specific surgical settings.
Keywords: venous thromboembolism; cancer surgery; network meta-analysis; direct oral anticoagulants; antithrombotic prophylaxis